Compatibility and optimization of antigen content to develop combined acellular diphtheria-tetanus-pertussis (DTaP) vaccine at Institute of Vaccines and Medical Biologicals - Nguyễn, Thị Thu Hoa; Nguyễn, Xuân Khánh Hà; Nguyễn, Văn Được; Trần, Ngọc Nhơn; Phạm, Thị Lan Anh; Lương, Thị Bích Trang; Nguyễn, Thị Lan Phương; Dương , Hữu Thái (Hue University Journal of Science: Natural Science, 2025)
Compatibility between components and the amount of antigens in combination vaccines are important factors determining the safety, efficacy, and stability of that vaccine. To develop the diphtheria-tetanus-acellular pertussis (DTaP) vaccine at the Institute of Vaccines and Medical Biologicals (IVAC), we evaluated the compatibility among the components and optimized the amount of antigens in the vaccine formulation. The antigen components, including tetanus antigen (T), diphtheria antigen (D), and recombinant pertussis toxoid (rPT), together with filamentous haemagglutination factor (FHA), and aluminum hydroxide adjuvant, were evaluated for compatibility by using physicochemical and immunological methods. Design Expert version 12 software was used to optimize the amount of each antigen in the DTaP vaccine formulation. The results show that the components are compatible with each other. The optimal DTaP vaccine formula contains 40 Lf/mL D, 20 Lf/mL T, 10 µg/mL rPT, 20 µg/mL FHA, and 0.6 mg Al3+/mL respectively, corresponding to the diphtheria potency of 94,47 IU/mL, tetanus potency of 107,86 IU/mL, and pertussis potency of 9,65 IU/mL. The DTaP vaccine developed by IVAC meets the standard of the Vietnamese Pharmacopoeia V, 2018, of the Ministry of Health, and WHO.